Pengaruh Media Video Pembelajaran Terhadap Motivasi Belajar Anak Usia 5-6 Tahun - Mardhian Ningrum, Anggun; Tri Sayekti; Ratih Kusumawardani (Program Studi Pendidikan Islam Anak Usia Dini, Fakultas Ilmu Tarbiyah dan Keguruan, UIN Sunan Kalijaga, Yogyakarta, 2021)
Early childhood learning motivation requires guidance and encouragement from older people as a driving motivator. Learning activities in schools are less innovative and interactive, so learning media is needed to increase children's learning motivation. The purpose of the study was to determine the effect of learning video media on the learning motivation of children aged 5-6 years. This research refers to experimental quantitative research using a nonequivalent control group design model. Data collection techniques using observation instruments, as well as documentation. Data analysis used SPSS 22 with paired samples test. The subject of this research 30 children with the division of RA AR Ar Rahman class RA B as the experimental group totaling 15 children and RA Daarul Mukhlisin class RA B as the control group totaling 15 children. The results showed that the effect of learning video media on experimental group children before getting treatment (pre-test) got an average value of 33.87, and after getting treatment (post-test), the score was 36.80. The use of learning video media has a good influence in increasing the learning motivation of children aged 5-6 years. In addition, computer-based learning videos make children feel happy and interested, developing aspects of child development. The findings of this study contribute to knowledge about the importance of developing learning videos in early childhood education.